2013
DOI: 10.1007/s00253-013-5288-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of arylacetonitrilase production from Alcaligenes sp. MTCC 10675 and its application in mandelic acid synthesis

Abstract: Alcaligenes sp. MTCC 10675 has been isolated from soil sample using enrichment method and has nitrilase catalytic system which is highly specific for the hydrolysis of arylaliphatic nitriles. Optimization of culture conditions using response surface methodology and inducer-mediated approach enhanced arylacetonitrilase production significantly (2.4-fold). Isobutyronitrile acted as an effective inducer for the induction of arylacetonitrilase, and it is highly specific for arylacetonitriles (phenyl acetonitrile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Alcaligenes sp. MTCC 10675 (isolated from soils of Shimla District of Himachal Pradesh, India, as a nitrile‐metabolizing bacterium and identified at the Microbial Type Culture Collection and Gene Bank, Institute of Microbial Technology, Chandigarh, India, was grown overnight in a seed medium (nutrient broth), and 1 mL of the seed culture was transferred into a 250 mL Erlenmeyer flask containing 50 mL of production medium (pH 7.0) consisting of (g/L) peptone 5.5 g, malt extract 3.0 g, yeast extract 5.5 g, and isobutyronitrile 4.0 g (60 mM) at 30 °C for 24 H . After 24 H, cells were separated from the culture broth by centrifugation at 10,000 g , washed twice with 0.1 M K 2 HPO 4 /KH 2 PO 4 (pH 7.0), and suspended in the same buffer containing 1 mM dithiothreitol (DTT) and 1 mM ethylenediaminetetraacetate (EDTA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcaligenes sp. MTCC 10675 (isolated from soils of Shimla District of Himachal Pradesh, India, as a nitrile‐metabolizing bacterium and identified at the Microbial Type Culture Collection and Gene Bank, Institute of Microbial Technology, Chandigarh, India, was grown overnight in a seed medium (nutrient broth), and 1 mL of the seed culture was transferred into a 250 mL Erlenmeyer flask containing 50 mL of production medium (pH 7.0) consisting of (g/L) peptone 5.5 g, malt extract 3.0 g, yeast extract 5.5 g, and isobutyronitrile 4.0 g (60 mM) at 30 °C for 24 H . After 24 H, cells were separated from the culture broth by centrifugation at 10,000 g , washed twice with 0.1 M K 2 HPO 4 /KH 2 PO 4 (pH 7.0), and suspended in the same buffer containing 1 mM dithiothreitol (DTT) and 1 mM ethylenediaminetetraacetate (EDTA).…”
Section: Methodsmentioning
confidence: 99%
“…A nitrile‐degrading bacterium Alcaligenes sp. MTCC 10675 has been isolated in our laboratory, which has high affinity for arylacetonitriles . In this article, purification, characterization, and sequence analysis of the amino acid sequence of arylacetonitrile‐hydrolyzing nitrilase of Alcaligenes sp.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the hydrogenation of CO double bonds of α-ketoesters and α-ketoacids has a special importance, because the corresponding chiral α-hydroxyacids stand out for their synthetic and biological relevance (Scheme ). For example, ( R )-(−)-mandelic acid (R = Ph) is an important pharmaceutical ingredient, whereas both enantiomers of 3-phenyllactic acid (R = CH 2 Ph) are antimicrobial agents active against bacteria and fungi, and the same synthons are claimed as monomers of bioderived aromatic polymers. , …”
Section: Introductionmentioning
confidence: 99%
“…Nitrilases differ variably in substrate specificities and find wide application in the transformation of a range of nitriles to acids (Sharma et al 2006(Sharma et al , 2012Bhatia et al 2014). Previous studies have revealed that nitrilases are specific for aromatic nitriles while nitrile hydratase has affinity towards aliphatic nitriles, but in light of rapidly growing information regarding nitrile metabolizing enzymes, various aspects have to be reconsidered (Mylerova and Martinkova 2003).…”
Section: Introductionmentioning
confidence: 99%